Effect and fate study with blue mussels and microplastic in a laboratory experiment: O2 depletion over time - Aurelia Laubscher; Thea Hamm; Mark Lenz (PANGAEA, 2021)
Adult blue mussels (Mytilus spp.) were exposed to microplastic particles in a controlled laboratory experiment. A significant loss of PS beads in pilot studies was traced back to the aeration of the exposure units. Therefore, the aeration was paused during the exposure phase of 2 hours. In a pilot study, the oxygen saturation was measured over 2 hours with mixing every 20 min in four treatment groups: with or without mussel in an aerated or non-aerated (static) set-up. Oxygen saturation lowered to 96.0 % (equivalent to 9.6 mg O2/ml) at the end of the 2 hours of exposure in the non-aerated set-up with mussels due to their respiration.
In: Laubscher, A et al. (2021): Effect and fate study with blue mussels and microplastic in a laboratory experiment [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.937475